Estimation of human motion using a simplified human-body dynamics model - Tatsuo UNNO (The Japan Society of Mechanical Engineers, 2017)
Recently, in vehicle development, consideration of the human passenger/driver has become increasingly important. In the present study, numerical simulation of human-body dynamics for a human in a vehicle was conducted. Generally, humans are simulated using whole-body models during numerical simulation. However, the whole-body model has multiple degrees of freedom and multiple properties that must be considered. Moreover, the influence of parameters of the human body is uncertain, and it is difficult to accurately set these parameters. Therefore, we herein focus on motion control of the human head and trunk because these parts account for a large portion of the overall human body. A simplified human model that can identify the characteristics of motion control for actual human response was proposed. In the present paper, the parameters of this human motion control are identified based on results obtained experimentally and using a simulation model. The characteristics of motion of an individual human are then considered based on the obtained characteristics of the parameters.